Designing of Adaptive Model-Free Controller Based on Output Error and Feedback Linearization - S. Pezeshki; M. A. Badamchizadeh; S. Ghaemi; M. A. Poor (Abstract and Applied Analysis)
This paper introduces a new approach to design Model-Free Adaptive Controller (MFAC) using adaptive fuzzy procedure as a feedback linearization based on output error. The basic idea is to transfer the control signal to an appropriate surface and then, depending on the output error of system, the control signal changes around this surface. Some examples are provided as well to illustrate the efficiency of the proposed approach. The obtained simulation results have shown good performances of the proposed controller.